Modeling sea surface current circulation from satellite altimetry data by using first order volterra model - Marghany, Maged; Hashim, Mazlan; Cracknell, Arthur P. (2007)
This paper introduces a new technique for acquiring accurate sea surface current from AVISO satellite altimetry data. The new technique was involved Volterra series expansion in order to transform the time series satellite altimetry data into a real ocean surface current. The basic equation of hydrodynamic has been solved by first order Volterra model. Then, the Volterra kernel inversion used to obtain the sea surface current velocity. The finite element model of Lax-Wendorff schemes was used to model the spatial current variations in the South China Sea during March 2003, April 2004 and March 2005. In situ sea surface current measurements were collected along the east coast of peninsular Malaysia by using Valeport electro-magnetic. The result shows that the integration between Volterra model and Lax-Wendroff scheme provides a means as a complementary tool to model sea surface current variations from AVISO satellite altimetry data with r2 value of 0.910 and root mean square error (RMSE) of Â±0.4 m/s.